Atomistic simulations of the local slip resistances in four refractory multi-principal element alloys. (February 2022) - Romero, Rebecca A.; Xu, Shuozhi; Jian, Wu-Rong; Beyerlein, Irene J.; Ramana, C.V.
Highlights: The local slip resistances (LSRs) are calculated for the 110, 112, and 123 planes in four MPEAs. The two MPEAs with Cr have larger lattice distortion than without. A larger lattice distortion results in increased LSR and reduced anisotropy in LSR. Abstract: The design and development of structural materials that can survive under the extreme conditions of operation are critical to next generation aerospace and energy technologies. Selectively designed multi-principal element alloys (MPEAs), which are solid solution phases with three or more principal elements on simple underlying lattices, are expected to fulfill such requirements. The combination of refractory metals with elements known for enhancing oxidation resistance, high temperature strength, and thermal stability makes them ideal candidates for high temperature applications. Due to their unique microstructures and chemical compositions, MPEAs may exhibit excellent mechanical properties, such as high strengths at elevated temperatures and improved hardnesses. Improving the mechanical properties of MPEAs requires knowledge of their plastic deformation mechanisms, at the core of which is dislocation slip, which is intimately connected to the local slip resistances (LSRs). In this work, atomistic calculations are conducted to obtain LSRs of edge and screw dislocations on three slip planes – 110, 112, and 123 – in four refractory MPEAs, CrMoNbTa, CrNbTaW, MoNbTaV, and MoNbTaW.The goal of this work is to determine the LSR and the role that lattice distortion has. We find that the two MPEAs containing Cr bear an increased lattice distortion and achieve the highest LSR values and lowest anisotropy in LSR. It is also shown that the MPEAs possess much lower slip resistance anisotropy than pure metals.